1990
DOI: 10.1042/cs0780261
|View full text |Cite
|
Sign up to set email alerts
|

A sensitive radioimmunoassay measuring endothelin-like immunoreactivity in human plasma: Comparison of levels in patients with essential hypertension and normotensive control subjects

Abstract: 1. A radioimmunoassay has been developed for measuring endothelin-like immunoreactivity in human plasma using an antibody raised against endothelin-1 which also cross-reacts with big endothelin-1 and endothelin-2 but not endothelin-3. 2. The sensitivity of the assay was 1 fmol/tube with inter- and intra-assay coefficients of variation of 13% and 9%, respectively. Cross-reactivity with endothelin-3 and non-endothelin peptides was less than 1%. 3. Endothelin-like immunoreactivity was present in the plasma of hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
60
2
1

Year Published

1992
1992
2007
2007

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 192 publications
(69 citation statements)
references
References 0 publications
6
60
2
1
Order By: Relevance
“…In situ hybridization with antisense ET-1 mRNA revealed increased ET-1 mRNA expression in the resistance vessels of subjects with essential hypertension. 28 In keeping with this finding, some investigators, 13,18 but not others, 29,30 have found elevated plasma ET-1 levels in subjects with hypertension. However, the majority of ET-1 is released abluminally, and increased production might not raise plasma levels substantially.…”
Section: Increased Endogenous Et-1 Activity In Hypertensionmentioning
confidence: 73%
“…In situ hybridization with antisense ET-1 mRNA revealed increased ET-1 mRNA expression in the resistance vessels of subjects with essential hypertension. 28 In keeping with this finding, some investigators, 13,18 but not others, 29,30 have found elevated plasma ET-1 levels in subjects with hypertension. However, the majority of ET-1 is released abluminally, and increased production might not raise plasma levels substantially.…”
Section: Increased Endogenous Et-1 Activity In Hypertensionmentioning
confidence: 73%
“…ET-1 is mainly released albuminally from the endothelium towards the underlying smooth muscle, and it is rapidly cleared from the circulation. In arterial hypertension high-to-low circulating values of ET-1 have been reported, 15,29,30 probably due to different methods of assay and different normal range, wideness of the population studied as well as different criteria of enrolment employed. Therefore, it is clear that there are a few difficulties in interpreting the significance of plasma ET-1 concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…4 Indeed, the potentiation of serotonininduced contractions by ET-1 might increase the vasospasms induced by aggregating platelets. Moreover, there is a positive correlation between ET-1 plasma level and systolic blood pressure in humans, 9 and the vascular production of ET-1 under angiotensin II (Ang II) stimulation is higher in hypertensive than in normotensive rats. 10 The amplification is nevertheless blocked by Ca 2+ entry blocker in human arteries 4 and in the rat mesenteric bed.…”
Section: Camentioning
confidence: 99%